Dry pleurisy complicating solitary pulmonary nodules caused by Mycobacterium avium: a case report. (December 2015) - Asakura, Takanori; Ishii, Makoto; Haraguchi, Mizuha; Kamiyama, Ikuo; Kohno, Mitsutomo; Sakamaki, Hiroyuki; Emoto, Katsura; Hayashi, Yuichiro; Sugiura, Hiroaki; Kawada, Ichiro; Soejima, Kenzo; Namkoong, Ho; et al.
Abstract Introduction Mycobacterium avium complex (MAC) lung disease presenting as a solitary pulmonary nodule (MAC-SPN) is often asymptomatic, is more common in middle to old age, and mimics lung cancer or tuberculoma. We report herein a case of MAC-SPN in an immunocompetent young adult patient, presenting with persistent chest pain and a subacutely progressive nodule with high intense18 F-fluorodeoxyglucose uptake. Histological examination of resected specimens revealed pleurisy, which is a rare finding of MAC-SPN. Case presentation A 36-year-old Japanese male presented with chest pain and a subacutely progressive pulmonary nodule. Positron emission tomography-computed tomography showed high intense18 F-fluorodeoxyglucose uptake in the nodule. Owing to his continuous chest pain and subacutely progressive nodules, wedge resection was performed using video-assisted thoracoscopic surgery. Histological examination revealed an epithelioid granuloma and pleurisy, and the lung tissue culture was positive for mycobacteria identified asM. avium . Conclusion This is the first report of MAC-SPN occurring with persistent chest pain, suggesting that MAC should be considered in the differential diagnosis of a solitary pulmonary nodule, even for patients who experience persistent chest pain. As in the present case, surgical resection with video-assisted thoracoscopic surgery is a reasonable approach to the diagnosis and treatment of MAC-SPN with possible malignancy, especially as MAC can be diagnosed using resected lung tissue culture with histological confirmation.